On‐Chip Supercapacitors: All‐Solid‐State On‐Chip Supercapacitors Based on Free‐Standing 4H‐SiC Nanowire Arrays (Adv. Energy Mater. 17/2019). Issue 17 (2nd May 2019) - Li, Weijun; Liu, Qiao; Fang, Zhi; Wang, Lin; Chen, Shanliang; Gao, Fengmei; Ji, Yuan; Yang, Weiyou; Fang, Xiaosheng
Abstract : In article number1900073, Weiyou Yang, Xiaosheng Fang and co‐workers report all‐solid‐state on‐chip SiC supercapacitors based on free‐standing SiC nanowire arrays, with a specific area energy and power density up to 5.24 μWh cm −2 and 11.2 mW cm −2, respectively, as well as robust stability with over 94% capacitance retention after 10000 cycles at 100 mV s −1 .